Immunological suppression by human CD8+ T cells is receptor dependent and HLA-DQ restricted. - Salgame, P (1991)
Mechanisms of specific immunologic unresponsiveness or tolerance and their regulation by the major histocompatibility complex remain central issues in immunology. Recent findings that potentially reactive anti-self T cells are not completely clonally deleted in the thymus and that specific immunological unresponsiveness can be acquired in certain infectious diseases, such as leprosy, suggest that peripheral unresponsiveness can be developed and maintained in adults. Human antigen-specific T suppressor cells represent one mechanism of peripheral tolerance. Clones of CD8+ T suppressor cells have been derived from blood or lesions of patients with lepromatous leprosy who are selectively unable to mount cellular immunity to Mycobacterium leprae. Using a panel of M. leprae-specific CD4+ and CD8+ T-cell clones of differing major histocompatibility complex class II haplotypes, suppression in vitro was found to be restricted by HLA-DQ and not by HLA-DR and inhibited by antibodies to HLA-DQ. In addition, antigen-induced suppression could be inhibited by antibodies specific to appropriate polymorphic T-cell receptor beta chains of the CD8+ clones. The results establish that activation of specific T suppressor cells is dependent on their polymorphic T-cell receptors and suggest that HLA-DQ serves as the preferred restricting element for suppression.